A simple method to establish calcite:aragonite ratios in archaeological mollusc shells. (11th December 2015) - Loftus, Emma; Rogers, Keith; Lee‐Thorp, Julia
ABSTRACT: Oxygen isotope thermometry from archaeological mollusc shells relies on preservation of the original crystal structure; in particular that metastable aragonite has not undergone recrystallization to calcite. Conventional methods for detecting recrystallization, however, require large sample sizes and extensive calibration, so that they cannot address variable shifts across sampling surfaces and in practice are rarely fully applied. Here we show that attenuated total reflectance Fourier transform infrared spectroscopy (FTIR‐ATR) can be applied to rapidly quantify biogenic aragonite and recrystallized calcite contents in mollusc shells at a sufficient level of accuracy. We established a series of calibration curves based on artificial mixtures of calcite and aragonite for comparison with archaeological samples. This method offers an improvement over existing tools. Most importantly, spectra can be determined from small samples that can be recovered for subsequent isotope analysis, thus allowing assessments of crystal structure at high spatial resolution across the shell surface and within an entire assemblage.